Patients with epilepsy care experiences: Comparison between services with and without an epilepsy specialist nurse. - Elliott, Naomi; Higgins, Agnes; Doherty, Colin; Begley, Cecily; Downes, Carmel; Varley, Jarleth; Tyrell, Ella; Normand, Charles (My University, 2018)
The aim of this study was to determine whether there were differences in experiences of care, satisfaction with care and quality of life between those who were in receipt of care from a service with an epilepsy specialist nurse (ESN) and those who were receiving care from a service that did not include an ESN. A comparative design was used, which involved the completion of a confidential, self-completed survey. The survey was administered to a nonprobability convenience sample of patients with epilepsy who were attending services with an ESN (n = 244) and services where the treatment team did not include an ESN (n = 261) from each of the four health areas in Ireland. This study found that, in comparison to people with epilepsy (PWE) who attended a service without an ESN, PWE who attended a service with an ESN reported receiving greater amount of information, were more involved in their care, perceived care to be better coordinated, and had greater confidence in the information provided and greater comfort in discussing issues with an ESN. They also reported higher rates of satisfaction with the emotional and practical support offered. Thus, it may be concluded that models of care involving the input of ESNs enhance the quality of epilepsy care and care processes. The findings also emphasize the need to have an ESN as part of the multidisciplinary team.
Keywords: Epilepsy; Specialist nurse; Advanced practice; Impact; Comparative study; Service delivery; Inclusive Society; Chronic Health Condition; Epilepsy